Potential of Cocoa Extract (Theobroma cacao) in Inhibiting Erythrocyte Damage Induced by Physalia utriculus Venom - Adinningtyas Intansari; Al Munawir; Laksmi Indreswari (Journal of Agromedicine and Medical Sciences, 2020)
Physalia utriculus is one of the invertebrate marine biota that is often found in Indonesia. Some symptoms of venoming due to jellyfish stings cause pain, itching, and hemolysis. In Indonesia, 13 cases of jellyfish stings were reported in 2005-2009 with three people dying in Java, Bali, and Bangka. Cocoa beans (Theobroma cacao L.) contain fat, carbohydrates, proteins, and polyphenol compounds that are useful as antioxidants. Polyphenols in the form of epicathechins, catechins, and procyanidins serve to provide protection to hemolysis. The purpose of this study was to determine the potential of ethanol extract of cacao (Theobroma cacao L.) in inhibiting the damage of erythrocyte induced by Physalia utriculus in vitro. This study used 28 samples of erythrocytes divided into seven groups, namely the normal control group, negative controls, and treatment with cocoa ethanol extract 0.2%, 0.1%, 0.04%, and 0.02%. Each subsequent group induced venom Physalia utriculus. The results showed that the average speed of erythrocyte lysis in the treatment group by giving cocoa ethanol extract 0.2%, 0.1%, 0.04%, and 0.02% respectively (seconds ± standard deviation) was 858,25 ± 94,44; 1.000,5 ± 159,93; 678,5 ± 19,71; and 1.006 ± 159,50. The mean speed of erythrocyte lysis in the negative control group was 1,025 ± 164.63 and the positive control group with the administration of N-Acetylcystein can last up to one hour after administration of venoms. Test for normality and homogeneity shows that data is normally distributed and homogeneous. One Way Annova analysis shows the significance value of p <0.05, then a post hoc analysis test was performed with the Bonferoni method to find out the differences in significance in each group. In this study it can be concluded that the administration of cocoa ethanol extract has no potential to inhibit erythrocyte damage that has been venomed by Physalia utriculus in vitro. Keywords: Physalia utriculus, cacao, erythrocyte damage